Synthesis, characterization and catalytic properties of titanium containing silica aerogel - Lee, Soon Chai (2005)
Silica aerogel and titania silica aerogel were synthesized by chemical means. The effect of titanium source, sulphuric acid and titanium loading were studied. The structure and properties of the aerogels were examined by X-ray diffraction (XRD), scanning electron microscopy (SEM), nitrogen adsorption (BET), energy dispersive X-ray analysis (EDX), Fourier transform infrared (FTIR), and ultra violet-visible diffuse reflectance spectroscopy (UV-Vis DRS). Both silica aerogel and titania silica aerogel are amorphous. The surface area of the resulting titania silica aerogel was significantly affected by the quantity of the acid used during synthesis. The physicochemical properties were found could be engineered by the change of acid loading and titanium loading. Isolated titanium in tetrahedral framework position, well dispersed titania particle or crystalline titania (anatase) were formed in-situ during the aerogel synthesis process. Catalytic reaction of cyclohexene and hydrogen peroxide was carried out at 70 Â°C in a fixed batch reactor. The effects of physicochemical properties of the catalyst, solvent, reaction temperature, oxidant content and alkene to the reaction have been investigated. Both allylic and nonallylic oxidation process have occurred in the reaction. 1,2-cyclohexanediol was formed as major compound in the reaction.